The Teacher Monologues - Carter, Mindy R. author. aut Link
XX, 124 p.
Keywords: This book examines the experiences of four Conservatory style trained actors, who go onto complete teacher education programs. In keeping with a/r/tography this research uses social science methods and creative methods of data collection. Interviews and reflective writing about the participant’s educational and experiential backgrounds are complimented by the writing of monologues. Themes from the data collected during interviews, reflective writing and monologues led to the understandings that: there is a connection between developing consciousness and having a noetic experience; actor-teachers want to talk about their noetic experiences; residue is an a/r/tographic rendering used to describe the way that having an illuminating experience in theatre school affected the participants; and an immanent curriculum can be understood by theatrical engagement. In addition to exploring the interview data and monologues, time is spent understanding the works of Antonin Artaud, a prolific theatre artist and a/r/tography, a method of arts-based research. This theoretical and a/r/tographical investigation leads to the creation of Interludes. These Interludes, theorized as rhizomatic curricular offshoots, allow for multiple entry points into these new understandings and provide an example of how to bring together artful inquiry into an academic arena. AWARDS: 2013 American Educational Research Association (AERA) Arts Based Educational Research (ABER) Dissertation Honorable Mention 2013 Canadian Society for the Study of Education (CATE) Canadian Association of Teacher Education (CATE) PhD Dissertation Award of Distinction Link to Info: Link Dr. Mindy R. Carter is an Assistant Professor at McGill University in the Department of Integrated Studies in Education. She has taught a range of education courses specializing in arts education and curriculum theory. Her research focuses on a/r/tography, teacher identity, teachereducation, arts based educational research and curriculum. Her publications have addressed knowledge mobilization, democracy and arts education, the impact of autobiographical and a/r/tographical dispositions on teacher candidates and the impact of creating art on teacher’s pedagogical development and identity. She is actively involved in local and international arts education organizations.